Preservice Preschool Teacher’s Phenomenological Understanding of Environment: A Projection to Education for Sustainable Development - Deniz Kahriman-Pamuk; Berat Ahi (Journal of Education in Science, Environment and Health)
The current study aims to understand the expectations of pre-service preschool teachers regarding what kind of environment we will live in in the future and the reasons behind these expectations in terms of sustainable development (SD). To this end, the current study was conducted based on a phenomenological model with the participation of 77 pre-service preschool teachers. The participating pre-service teachers were first asked to draw the future environment they expect to see. Subsequently, they were interviewed and asked to explain their drawings and why they hope to see that environment in the future. According to the study, most pre-service teachers have negative expectations about the future environment. On the other hand, there are a few positive and technology-oriented expectations. Furthermore, a significant portion of the participants explained the environmental dimension of SD. On the other hand, a small number of participants preferred to explain different pillars together by creating cause-and-effect relationships. Given the obtained findings, it is suggested that environmental education should be more widespread at every level of schooling. The political, economic, and social pillars of SD should be more extensively incorporated into the existing curriculums.